Programmable Hierarchical Construction of Mixed/Multilayered Polysaccharide Nanocapsules through Simultaneous/Sequential Nanoprecipitation Steps - Yan, Xibo; Ramos, Ricardo Almeida Neves Sampayo; Alcouffe, Pierre; Munoz, Luis Enrique; Bilyy, Rostyslav O.; Ganachaud, François; Bernard, Julien (Biomacromolecules, 2019)
We report here on a one-pot construction of oil-filled hierarchical capsular assemblies using the nanoprecipitation technique. Relying on multicomponent phase diagrams, we show that simultaneous and/or sequential nanoprecipitations involving polymer combinations can be precisely programmed to design a new class of mixed/multilayered multicomponent nanocapsules, with a precise control of the dimensions, shell thickness/composition, and spatial distribution of the building blocks. The simplicity and tunability of this approach are exemplified here with a library of neutral and ionic polysaccharides giving access to a range of functional multilayered nanocarriers of interest for biomedical applications.
CRIS-Team Scopus Importer:2019-10-15